Granjas leiteiras na região de Ribeirão Preto - SP - Milani, Adhemar P. [UNESP]; de Souza, Fernando A. [UNESP] (FapUNIFESP (SciELO), 2010)
On the activities of dairy farm, the constructions for the animals are basic and of utmost importance in the production process, their designs should be based on technical and economic solutions, which offer extremely efficient and functional conditions. The objectives of this work was to research and study the characteristics of dairy farms located in some towns near Ribeirão Preto and the south of Minas Gerais State and recommend solutions based on the literatures for the execution of dairy projects around Ribeirão Preto region. The study was conducted based on theoretical and in loco observations, considering the following parties of dairy farm: free stall, calves housing, milking room and its annexes (footbath, foot clean and waiting corral). The results obtained of this study appeared that most of the dairy farms were designed without technical and effective economical solutions.
Dairy farms at Ribeirão Preto region - SP, Brazil
Keywords: Dairy cattle; Dairy farm; Rural construction